CONSTRUCTION OF WOMANHOOD IN THE BENGALI LANGUAGE OF BANGLADESH - Mahmood, Raassheed (POLISSEMA – Revista de Letras do ISCAP, 2019)
The present essay attempts to explore the role of gender-based language differences and of certain markers that reveal the status accorded to women in Bangladesh. Discrimination against women, in its various forms, is endemic in communities and countries around the world, cutting across class, race, age, and religious and national boundaries. One cannot understand the problems of gender discrimination solely by referring to the relationship of power or authority between men and women. Rather one needs to consider the problem by relating it to the specific social formation in which the image of masculinity and femininity is constructed and reconstructed. Following such line of reasoning this essay will examine the nature of gender bias in the Bengali language of Bangladesh, holding the conviction that as a product of social reality language reflects the socio-cultural behaviour of the community who speaks it. This essay will also attempt to shed some light on the processes through which gender based language differences produce actual consequences for women, who become exposed to low self-esteem, depression and systematic exclusion from public discourse.